EFFECTIVENESS OF GROUP COUNSELING ON INTERNET ADDICTION AMONG COLLEGE STUDENTS IN SELECTED COLLEGES IN CHENNAI - S. Umadevi; M. Abirami (The Bioscan, 2025)
Background: The term “internet addiction” is mentioned, it refers to the internet usage of an individual, to the extent that it becomes compulsive and makes it impossible for the individual to carry out his/her routine life, work and social function. Methodology: A quasi-experimental research design using pretest, post-test design was used. The study was designed for a total time of four months, which include two months for intervention and two months for post evaluation. The study was conducted in selected colleges in Chennai, colleges and students meeting the inclusion criteria were purposively sampled. Results: The result showed that after the intervention, the study shows a significant reduction in internet addiction indicated by the mean score falling from 56.4 (SD = 10.1) to 43.2 (SD = 8.7), t = 7.53, p = 0.000. The effectiveness of group counseling is proved by moderate addiction drop down (45.7%) and severe addiction (31.4%) while the mild addiction went up to 51.4% and the severe addiction went down to 14.3%. There were significant associations between educational level (p = 0.043), stream of study (p = 0.001), and internet usage (p = 0.000) and internet addiction. They were also related to education (p = 0.002) and marital status (p = 0.02), but age, gender, socio-economic status, and having a mental health history were not associated with the degree of change in symptoms. Conclusion: The study concludes that group counseling successfully decreases the level of internet addiction in college students. The numbers of people in addiction decreased dramatically after the targeted interventions were implemented.